Al Mawardi's Thoughts on the Welfare State in the 1998-2019 Reform Era in Indonesia - Mustafa Mustafa (Sekolah Tinggi Agama Islam Taruna Surabaya, 2022)
The concept of a Welfare State is a country that discusses the principle of the balance of world morality and religious morality in every people. This study uses a normative, historical, and sociological approach, because it is closely related to Al-Mawardi's thoughts about the welfare state with the reform era in Indonesia in 1998-2018 as follows: First, the Religion aspect, Al-Mawardi makes religion a state ideology, while The Indonesian state uses an ideology known as Pancasila. Second, aspects of Good Governance. Al Mawardi's ideas and what is implemented in Indonesia are in principle the same, Indonesia applies the need for a professional government system, in terms of efforts to meet the needs of citizens; Third, the aspect of Justice, Al Mawardi highly upholds the existence of justice in a country, Indonesia also does the same. The State of Indonesia is a state of law (rechtsstaat), according to Article 1 paragraph (3) of the 1945 Constitution. All citizens are treated equally before the law (equality before the law); Fourth, the aspect of National Security, related to this, Al Mawardi hopes that state security can provide inner peace to the people, and ultimately encourage people to take the initiative and be creative in building the country. Indonesia also has a desire to build a nation. The Indonesian people always strive for state security which also creates a sense of security for citizens; Fifth, the aspect of Economic Prosperity. Al Mawardi views that prosperity can arouse human enthusiasm to improve work ethic, form various social associations between social classes, reduce levels of social tension, prevent conflict and hostility, create progress in all fields, and build harmony and social cooperation. In Indonesia, the trend of poverty since the 1998-2018 reform era has decreased, this proves that the State of Indonesia is also very concerned about the economy of its people. Sixth, The Nation's Vision. Al-Mawardi emphasized the importance of the entrepreneurial spirit and achievement motivation in the economy for future progress. Currently, Indonesia is very aggressively strengthening MSMEs and entrepreneurship. This is in line with Al-Mawardi's ideas regarding The Nation's Vision.